A qualitative content analysis of the experience of hypospadias care: The importance of owning your own narrative - Phillips, Lottie; Dennermalm, Nicklas; Örtqvist, Lisa; Engberg, Hedvig; Holmdahl, Gundela; Fossum, Magdalena; Möller, Anders; Nordenskjöld, Agneta (Frontiers in Pediatrics, 2023)
Objectives: There is a lack of studies on men’s individual experiences of living with hypospadias. We aimed to explore the personal experiences of having hypospadias in relation to healthcare and surgery. Subjects and methods: Purposive sampling was used to include men (aged 18 and over) with hypospadias representing different phenotypes (from distal to proximal) and ages in order to maximise the variation and richness of our data. Seventeen informants, aged 20-49, were included in the study. In-depth semi-structured interviews were conducted between 2019 and 2021. Inductive qualitative content analysis was used to analyse the data. Results: We identified three categories: 1. Having surgery, which comprised the decision to operate, the experience of having surgery, and the outcomes of surgery; 2. Going to the doctor, which focused on follow-up care, re-entering care in adolescence or adulthood, and the experience of healthcare interactions; 3. Being informed, both about hypospadias in general, as well as about your specific body and medical history. There was overall a large variation in experiences. The latent theme across the data was the importance of owning your own narrative. Conclusion: The experience of men with hypospadias in healthcare is complex and varied, highlighting the difficulty of fully standardised care. Based on our results, we suggest that follow-up should be offered in adolescence, and that ways of accessing care for late onset complications be made clear. We further suggest clearer consideration for the psychological and sexual aspects of hypospadias. Consent and integrity in all aspects and all ages of hypospadias care should be adapted to the maturity of the individual. Access to trustworthy information is key, both directly from educated healthcare staff and if possible, from websites or patient-led forums. Healthcare can play a key role in providing the growing individual with tools to understand and address concerns that may develop relating to their hypospadias through life, giving them ownership over their own narrative.